2012
DOI: 10.1112/jlms/jds030
|View full text |Cite
|
Sign up to set email alerts
|

Bridge and pants complexities of knots

Abstract: We modify an approach of Johnson to define the distance of a bridge splitting of a knot K in a 3-manifold M using the dual curve complex and pants complex of the bridge surface. This distance can be used to determine a complexity, which becomes constant after a sufficient number of stabilizations and perturbations, yielding an invariant of (M, K). We also give evidence toward the relationship between the pants distance of a bridge splitting and the hyperbolic volume of the exterior of K. Mathematics Subject Cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The other operation increases the number of arcs in τ i : Any bridge splitting of (Y, K) obtained by connected summing with the standard (0, 2)-splitting of the unknot in S 3 is said to be obtained by elementary perturbation, and any splitting obtained by a finite number of elementary perturbations is called a perturbation. As with Heegaard splittings and trisections, it is known that if two bridge splittings of (Y, K) have the same underlying Heegaard splitting, then there is a bridge splitting that is isotopic to perturbations of each of the original splittings, called a common perturbation [Hay98,Zup13], and thus any two bridge splittings of (Y, K) become isotopic after stabilizations and perturbations. The purpose of this section is to define perturbations for generalized bridge trisections and lay out steps toward a proof of a corresponding uniqueness theorem in this setting.…”
Section: Uniqueness Of Generalized Bridge Trisectionsmentioning
confidence: 99%
“…The other operation increases the number of arcs in τ i : Any bridge splitting of (Y, K) obtained by connected summing with the standard (0, 2)-splitting of the unknot in S 3 is said to be obtained by elementary perturbation, and any splitting obtained by a finite number of elementary perturbations is called a perturbation. As with Heegaard splittings and trisections, it is known that if two bridge splittings of (Y, K) have the same underlying Heegaard splitting, then there is a bridge splitting that is isotopic to perturbations of each of the original splittings, called a common perturbation [Hay98,Zup13], and thus any two bridge splittings of (Y, K) become isotopic after stabilizations and perturbations. The purpose of this section is to define perturbations for generalized bridge trisections and lay out steps toward a proof of a corresponding uniqueness theorem in this setting.…”
Section: Uniqueness Of Generalized Bridge Trisectionsmentioning
confidence: 99%
“…If Σ 2 is an elementary perturbation of Σ, then Σ 2 is a (g, b + 1)-surface. Given any two bridge surfaces Σ 1 and Σ 2 for (M, J), there is a third bridge surface Σ * which can be obtained from either Σ i by elementary perturbations and stabilizations [26].…”
Section: Preliminariesmentioning
confidence: 99%
“…In Theorem 2.2 of [32], it is shown that any two bridge splittings for a link L in S 3 have a common perturbation. Although Theorem 2.2 is stated for B = S 3 , the verbatim proof suffices in the case that ∂B, ∂T = ∅, and so we do not include it here.…”
Section: Stable Equivalence Of Bridge Trisectionsmentioning
confidence: 99%
“…Theorem 7.1. [32] Suppose that Σ 1 and Σ 2 are bridge splittings for a tangle T in a punctured 3-sphere B. Then there is a surface Σ * which is a perturbation of both surfaces.…”
Section: Stable Equivalence Of Bridge Trisectionsmentioning
confidence: 99%